KEBERLANJUTAN DISEMINASI INFORMASI PUBLIK DI ERA PANDEMI COVID-19 - Doni Darmasetiadi (Fakultas Ilmu Sosial dan Ekonomi, Universitas Respati Yogyakarta, 2021)
ABSTRACTThe Covid-19 pandemic due to a novel virus yet infectious disease needs to be informed to the public. This process was implemented due to a gap in information from the public regarding knowledge of the Covid-19 pandemic. This very circumstance requires the continuity of public information dissemination in Indonesia. This study aims to examine the sustainability of public information dissemination in the era of the Covid-19 pandemic; to describe the meaning of the role of public information in the era of the Covid-19 pandemic. This study employs a literature study to determine concepts and discussions in the conditions of the Covid-19 pandemic. This study employs the concept of public information, dissemination, and principles of sustainable development. In addition, this study refers to a number of government regulations, namely: KMK-No.-HK.01.07 MENKES 413 2020 concerning Guidelines for the Prevention and Control of Covid-19, Law No. 14 of 2008 concerning Public Information Disclosure, and the Minister of Communication and Informatics Regulation Number 17/Per/M.Kominfo/03/2009 concerning National Information Dissemination by the Government, Provincial Governments and Regency/City Governments. Furthermore, the study is related to the condition of the Covid-19 pandemic. This study concludes that the sustainability of public information dissemination in the Covid-19 pandemic era can be implemented if it is applied with the concept and several applicable requirements, namely the quality of information, optimization of dissemination, and the adoption of the principle of sustainable development in the dissemination of public information.Keywords: Covid-19 pandemic, information public, dissemination, sustainable development principle. ABSTRAKPandemi Covid-19 yang disebabkan oleh penyakit baru dan menular perlu diinformasikan kepada publik. Proses ini dilakukan karena adanya kesenjangan informasi dari publik terkait pengetahuan pandemi Covid-19. Kondisi ini memerlukan adanya keberlanjutan diseminasi informasi publik di Indonesia.Kajian ini bertujuan untuk untuk mengkaji keberlanjutan diseminasi informasi publik di era pandemi Covid-19; untuk menguraikan pemaknaan perana informasi publik di era pandemi Covid-19. Kajian ini menggunakan studi kepustakaan untuk menemukan konsep dan pembahasan dalam kondisi pandemi Covid-19.Kajian ini menggunakan konsep dari informasi publik, diseminasi, dan prinsip pembangunan berkelanjutan. Selain itu, kajian ini juga merujuk pada sejumlah peraturan pemerintah, yakni: KMK-No.-HK.01.07 MENKES 413 2020 tentang Pedoman Pencegahan dan Pengendalian Covid-19, Undang-Undang No. 14 Tahun 2008 tentang Keterbukaan Informasi Publik, dan Permen Kominfo Nomor 17/Per/M.Kominfo/03/2009 tentang Diseminasi Informasi Nasional oleh Pemerintah, Pemerintah Daerah Provinsi dan Pemerintah Daerah Kabupaten/Kota. Selanjutnya, kajian dikaitkan dengan kondisi pandemi Covid-19. Kajian ini menyimpulkan bahwa keberlanjutan diseminasi informasi publik di era pandemi Covid-19 dapat dilakukan jika dilakukan dengan konsep dan beberapa persyaratan yang berlaku, yakni kualitas informasi, optimalisasi diseminasi, dan adopsi prinsip pembangunan keberlanjutan dalam diseminasi informasi publik. Kata Kunci: Pandemi Covid-19, informasi publik, diseminasi, dan prinsip pembangunan berkelanjutan